Answer is: a= -4
STEP
1
:
1
Simplify —————
a + 3
Equation at the end of step
1
:
a 3 1
(————————+—————)-——— = 0
((a2)-9) (a-3) a+3
STEP
2
:
3
Simplify —————
a - 3
Equation at the end of step
2
:
a 3 1
(————————+———)-——— = 0
((a2)-9) a-3 a+3
STEP
3
:
a
Simplify ——————
a2 - 9
Equation at the end of step
3
:
a 3 1
(————————————————— + —————) - ————— = 0
(a + 3) • (a - 3) a - 3 a + 3
Equation at the end of step
4
:
(4a + 9) 1
————————————————— - ————— = 0
(a + 3) • (a - 3) a + 3
Pull out like factors :
3a + 12 = 3 • (a + 4)
Equation at the end of step
6
:
3 • (a + 4)
————————————————— = 0
(a + 3) • (a - 3)
3•(a+4)
——————————— • (a+3)•(a-3) = 0 • (a+3)•(a-3)
(a+3)•(a-3)
a+4 = 0
Subtract 4 from both sides of the equation :
a = -4
Answer:
x²-2x-99
Step-by-step explanation:
(x-11)(x+9) - foil method
x times x = x squared
x times 9 = 9x
-11 times x = -11x
-11 times 9 = -99
x squared + 9x + 11x + -99
x squared-2x-99
Answer:
1/7
Step-by-step explanation:
Another word for multiplicative inverse is reciprocal
It is the number that when multiplied by the original number gives you one
7 * x = 1
Divide by 7
7x/7 = 1/7
x = 1/7
The multiplicative inverse of 7 is 1/7
Answer:
option 3.75°
Step-by-step explanation:
we know that
If two triangles are similar, then the corresponding angles are congruent
so
In this problem
The corresponding angles are
m∠A and m∠D, m∠B and m∠E, m∠C and m∠F
so
m∠A=m∠D
m∠B=m∠E
m∠C=m∠F
therefore
m∠F=75°